2019
DOI: 10.3390/cancers11081097
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I (ApoA-I), Immunity, Inflammation and Cancer

Abstract: Apolipoprotein A-I (ApoA-I), the major protein component of high-density lipoproteins (HDL) is a multifunctional protein, involved in cholesterol traffic and inflammatory and immune response regulation. Many studies revealing alterations of ApoA-I during the development and progression of various types of cancer suggest that serum ApoA-I levels may represent a useful biomarker contributing to better estimation of cancer risk, early cancer diagnosis, follow up, and prognosis stratification of cancer patients. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 201 publications
(231 reference statements)
1
123
0
2
Order By: Relevance
“…And in our study, the prognosis was poor when the BAR ratio was increased. This may be related to a decrease in ApoA-1 levels, as low concentrations of ApoA-1 are closely associated with the development, progression, and prognosis of multiple malignancies (18)(19)(20)(21)31). While ApoB's research focuses on cardiac metabolic disorders, the study found that individuals with higher ApoB levels might have a greater cancer mortality risk (31,32).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…And in our study, the prognosis was poor when the BAR ratio was increased. This may be related to a decrease in ApoA-1 levels, as low concentrations of ApoA-1 are closely associated with the development, progression, and prognosis of multiple malignancies (18)(19)(20)(21)31). While ApoB's research focuses on cardiac metabolic disorders, the study found that individuals with higher ApoB levels might have a greater cancer mortality risk (31,32).…”
Section: Discussionmentioning
confidence: 96%
“…Lysophosphatidylcholines, such as lysophosphatidic acid (LPA), are the proliferation activators of many tumors, and ApoA-1 can bind with LPA to inhibit the formation of tumors induced by LPA (35). In addition, there is an interaction between ApoA-1 and the body's inflammatory response, which reduces the rate of liver synthesis and secretion of ApoA-1, and serum low ApoA-1 concentration can indirectly lead to increased cytokine release and strong inflammatory response against tumor cells (20,34,36). Second, serum lipids inhibit the growth and metastasis of tumor cells by stabilizing the stability of prostaglandin 2 (PGI2) (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoprotein A-I (apoA-1), mainly synthesized by hepatocytes and intestinal cells, is the main component of high density lipoprotein (HDL) [2]. HDL has a versatile anti-atherosclerosis effect on the one hand, the second main feature is its anti-in ammatory properties [3,10].…”
Section: Discussionmentioning
confidence: 99%